Education and conflict : complexity and chaos - Davies, Lynn (RoutledgeFalmer, 2004)
This book is a critical review of education in an international context. Based on the author's extensive research and experience of education in several areas afflicted by conflict, it explores the relationship between schooling and social conflict.